Developing e-learning media on education statistics subject - Purnomo, E A; Dalyono, B; Lestariningsih, E D (Journal of physics. Conference series, 2021)
Lecturers as teachers must be able to create engaging, innovative learning based on ICT. Through this basis, it is necessary to develop e-learning learning media. Based on preobservation at UT students on the Education Statistics subject, it is concluded that 1). Student’s learning outcomes were lacking, 2). many students could only absorb theory but could not apply it to daily problems. One of the solutions to overcome these problems is by developing elearning media. Through the advantages of e-learning, e-learning learning media will be developed in the Education Statistics subject. This research aims to produce valid e-learning media. The subjects of this study were students of UT Semarang Pokjar Kendal district. The development of instructional media designs used the 4-D model from Thiagarajan, Semmel, and Semmel. Methods of data collection using questionnaires, interviews, and observations. The results showed that design of e-learning learning media was designed according to the characteristics of UT students. The validation results of 3 validators with an average of 4.1 with very valid category. The results of the legibility test were carried out twice with an average result of 87% which was included in the very good category.